Faktor-Faktor Protektif Dalam Menangguhkan Rencana Bunuh Diri (Studi Fenomenologi Pada Penyintas) - Roshinta Erezka; Ninil Elfira; Azmatul Khairiah Sari (Empowerment Counseling Journal, 2025)
Suicide is an unresolved global crisis. Trends indicate that suicides are increasingly being committed by adolescents, with over 51% of suicides occurring in those under 45. Previous research has noted that individuals who have attempted suicide have a negative and pessimistic outlook on life. This study aims to describe the meaning of individuals' experiences in postponing suicide. Suicide attempters were selected through snowball sampling. Data collection was conducted through phenomenological interviews and participant observation. Data analysis used descriptive phenomenological analysis to elicit the essence of suicidal experiences into phenomenological themes. This study identified three themes that can facilitate suicidal ideation: spirituality, family and hope. The implication of this research is that suicide prevention efforts can consider these findings as protective factors for individuals at risk of suicide and build support networks for suicide survivors.